Hpv-18 e2 Protein Downregulates Antisense Noncoding Mitochondrial Rna-2, Delaying Replicative Senescence of Human Keratinocytes - Borgna-Christie, V (Impact Journals LLC, 2019)
Human and mouse cells display a differential expression pattern of a family of mitochondrial noncoding RNAs (ncmtRNAs), according to proliferative status. Normal proliferating and cancer cells express a sense ncmtRNA (SncmtRNA), which seems to be required for cell proliferation, and two antisense transcripts referred to as ASncmtRNA-1 and -2. Remarkably however, the ASncmtRNAs are downregulated in human and mouse cancer cells, including HeLa and SiHa cells, transformed with HPV-18 and HPV-16, respectively. HPV E2 protein is considered a tumor suppressor in the context of high-risk HPV-induced transformation and therefore, to explore the mechanisms involved in the downregulation of ASncmtRNAs during tumorigenesis, we studied human foreskin keratinocytes (HFK) transduced with lentiviral-encoded HPV-18 E2. Transduced cells displayed a significantly extended replicative lifespan of up to 23 population doublings, compared to 8 in control cells, together with downregulation of the ASncmtRNAs. At 26 population doublings, cells transduced with E2 were arrested at G2/M, together with downregulation of E2 and SncmtRNA and upregulation of ASncmtRNA-2. Our results suggest a role for high-risk HPV E2 protein in cellular immortalization. Additionally, we propose a new cellular phenotype according to the expression of the SncmtRNA and the ASncmtRNAs. © Villota et al.